Shipping management simulation game for teaching and learning in higher education: A quasi-experimental study - Mohd Radzi, Shanizan Herman (Universiti Utara Malaysia Press, 2019)
Purpose - This study examines the effects of a simulation board game for teaching and learning shipping management in higher education. A framework of comprehensive shipping operations is developedaccording to the syllabus of the Shipping Management course at Universiti Utara Malaysia.The course core content in the game covers two main services—liner services and tramp services in the shipping industry.Methodology - A quasi-experimental research design was adopted to measure the effectiveness of the board game in giving students some understanding about shipping operations. Data were gathered from a sample of 73 undergraduate students enrolled in a Shipping Management course, using a non-equivalent control group design. The data were analysed using the McNemar Test to determine the level of understanding in shipping operations.Findings - It was found that using the board game in learning activities contributed to the improvement of students’ knowledge and skills. A performance comparison indicated that there were differences in students’ achievement for the tramp services and liner services contents.Significance - The framework for the shipping management board game aims to provide the best learning experience for students when they immerse themselves in solving problems and making decisions in the game. The framework can be used as a benchmark in the practice of game-based learning, particularly by affording students the opportunity to engage in learning by doing. Furthermore, this frameworkintroduces a tangible problem space through the board game, encouraging students to discover knowledge at their own pace in a non-threatening environment.